Кам’яна іконка із Звенигорода - Петегирич, В.; Оприск, В.; Закалик, Б. (Інститут українознавства ім. І. Крип'якевича НАН України, 2009)
The article deals with casual find of stone icon from Zvenyhorod. This artifact is made of pyrophyllite slate of dark-red color. It is round with rectangular ear with dimensions: 45x38x6,5–7,1 millimeters. Relief half-length picture of Christ with monogram “ІС–ХС” is placed on averse and image of flowering cross with two shoulders is scratched on reverse. The find belongs to local production of Zvenyhorod craftsmen oriented on common townsmen.